A whole-economy Deep Decarbonization Pathway for Mexico. (January 2021) - Buira, Daniel; Tovilla, Jordi; Farbes, Jamil; Jones, Ryan; Haley, Ben; Gastelum, Dennis
Abstract: Mexico's current climate change policy sets the country on a development pathway which is inconsistent with the goals of the Paris Agreement. The Deep Decarbonization methodology has been used to develop an alternative whole-economy pathway to 2050 consistent with limiting warming to between 1.5 and 2°C above pre-industrial times, covering energy and non-energy sectors and achieving comparable population and GDP growth to those expected from current policies. In this pathway, renewable electricity substitutes fossil fuels as the main energy source before 2040, urban regulation and infrastructure favor public transport while electric vehicles are rapidly rolled out to both public and private fleets, and improved agricultural and forest management practices reduce emissions and increase absorptions. Rapid uptake of renewable electricity and electric vehicles will require decisive policy action, and the resulting reductions in oil and gas demand will require changes to fiscal policy and industrial strategy. This work is part of the "Deep Decarbonization Pathways for Latin America" project. Highlights: Mexico's current climate policy is incompatible with Paris Agreement goals. The DDP methodology shows how Mexico can achieve these goals. Modal shift and electrification of urban transport rapidly reduce oil demand. Renewable electricity replaces fossil fuels as main source of energy before 2040. Lower agricultural emissions and greater forest absorptions are also required.